The Effect of Different Solvents on the Content of Black Cumin Seed Extract (Nigella sativa) - Hariutami, Desi; Darmawati, Sri; Permana, Atna; Zuraida, Zuraida (Jurnal Kefarmasian Indonesia, 2024)
Seeds of black cumin (Nigella sativa L.), also called "black cumin," are an herbal plant from the Ranunculaceae family. The objective of this study was to determine the yield of black cumin seed extract using 96% ethanol, N-hexane, and ethyl acetate as solvents, as well as to determine the results of phytochemical screening tests and the active ingredient content using GCMS. The stages of the research included the extraction process, phytochemical screening test, and GCMS. The study's findings on the yield of black cumin seed extract using the three solvents showed that the solvent N-Hexane produced the highest yield, at 28.09 percent. Based on phytochemical screening tests, black cumin seeds were positive for containing secondary metabolites such as alkaloids, saponins, phenolic flavonoids, triterpenoids, steroids, and glycoxides. Other potential compounds vizhexadecenoic acid, ethyl ester, Methyl (8e,11e)-8,11- octadecadienoate, 12-octadecadienoic acid (z,z)-, Grape seed oil.